Meta-analysis of association between caesarean section and postpartum depression risk - Ning, Jiajie; Deng, Jing; Li, Shanshan; Lu, Caina; Zeng, Pingping (Frontiers in Psychiatry, 2024)
Background The association of caesarean section (CS) for postpartum depression (PPD) remains controversial. This study aims to explore the relationship between CS and the risk of PPD, in order to provide a basis for preventing PPD. Material and methods We searched PubMed, Web of Science, Cochrane Library, and EMBASE databases for literature about the correlation between CS and PPD published as of February 2024. The combined odds ratios (ORs) and 95% confidence intervals (Cls) were obtained by flexible use of fixed-effects models or random-effects models. Results A total of 18 publications were ultimately included in the analysis. Among these, 14 were cohort studies and 4 were case-control reports, encompassing 844,328 total cases. All of the included studies were deemed to be of moderate or higher quality. The meta-analysis indicated that the prevalence of PPD among parturients undergoing CS was 13.4% (95% CI: 6.5%-25.5%).The adjusted odds ratio (OR) for the association between CS and PPD was 1.12 (95% CI: 1.04-1.20) compared to the natural vaginal delivery (NVD) group. Specifically, the adjusted OR for the association between CS and PPD was 1.29 (95% CI: 1.18-1.40) during the first 1-6 months postpartum, and 1.23 (95% CI: 1.14-1.33) after 6 months postpartum. Furthermore, in comparison to the NVD group, the adjusted OR for elective caesarean section (ELCS) and emergency caesarean section (EMCS) were 0.96 (0.83, 1.10) and 1.20 (1.08, 1.34), respectively. Conclusion Our findings suggest that PPD risk may rise in the presence of CS. In particular, the risk was increased by 20% in the EMCS group, and the risk of PPD within one to six months postpartum after CS increases by 6% compared to that at six months postpartum. In the future, more rational designs and in-depth studies are needed to obtain more accurate information. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#recordDetails, identifier CRD42023389265.